Deradikalisasi Agama Melalui Kegiatan Keagamaan di Masjid Kampus Ulul Azmi UNAIR Surabaya - Muhammad Syarif Hidayatulloh; Fitri Nurhidayati (State Institute of Islamic Studies (IAIN) Salatiga, 2019)
Various studies on radicalism in Non-Religion Higher Education show thatthe institutions are not sterile from this movement. If it is left, in the next few years, it will cause disintegration of the nation. Besides for worship, the campus mosque is the most effective means of spreading radicalism throughstructured studies among students. This study examines the efforts of the Ulul‘Azmi campus mosque of C Airlangga University in Surabaya to counteractradicalism among students. This study is a qualitative research with thedescriptive analysis. The results of this study indicate that the efforts for thecaretaker of the Ulul ‘Azmi mosque Airlangga University are by strengtheningmoderate Islamic ideology and nationalist insights and imposing strictpermits on study groups conducted by external organizations. The studymaterial is also determined by the mosque management with moderate andtolerant principles. This study is expected to be able to provide solutions forthe development of understanding of religious radicalism in universities through campus mosques